Integrating Technology in Indonesian EFL Classrooms: Why Not? - Gai Mali, Yustinus Calvin (Beyond Words, 2016)
The Minister of Education and Culture Republic of Indonesia, through its substantial policies, has gradually encouraged teachers in Indonesia to integrate the use of technology into their teaching practices. Responding to the policies, this paper aims to introduce Hot Potatoes, Blog, and Edmodo, as some alternative educational technology that the teachers can utilize to support their teaching practices, particularly in their English as a Foreign Language (EFL) classrooms. The paper addresses technological potentials of the technology for teaching and learning, such as for accessing information about the language, providing exposure to English, publishing learner work, interacting with other learners, managing, and organizing learning. The paper also explains possible challenges in utilizing the technology specifically in EFL teaching contexts. The discussions are supported with my reflective experience in utilizing the technology, related research findings, and literature. This paper provides insights into alternative educational technology that the teachers can use. Additionally, the paper can encourage the teachers to begin utilizing the technology to support their teaching practices and help students achieve learning objectives in their EFL classrooms.